2017
DOI: 10.1186/s12872-017-0598-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tolvaptan in patients with acute heart failure: a systematic review and meta-analysis

Abstract: BackgroundAcute heart failure, which requires urgent evaluation and treatment, is a leading cause for admission to the emergency department. The aim of this meta-analysis was to evaluate the effects of tolvaptan on acute heart failure and compare them with the effects of conventional therapy or placebo.MethodsThe electronic databases PubMed, EMBASE, and the Cochrane Controlled Trial registry were searched from their starting dates to October 24, 2016. Two authors independently read the trials and extracted rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 32 publications
4
52
0
Order By: Relevance
“…Consistent with our findings, a meta-analysis of tolvaptan studies in patients with acute HF (6 randomized controlled trials in 746 patients) reported improvements compared with control (placebo or conventional therapy) in body weight, serum sodium concentration and congestive symptoms, but without effect on short-term (≤30 days) or long-term (>30 days) all-cause death. 26 Our subgroup analyses showed that certain disease/patient factors affect the risk of death. Specifically, hyponatremia severity at baseline, the extent of tolvaptan-induced improvement in hyponatremia, and patients' ability to respond to tolvaptan with increased urine output are associated with lower 6-month all-cause death.…”
Section: Baseline Characteristics According To Outcomementioning
confidence: 81%
“…Consistent with our findings, a meta-analysis of tolvaptan studies in patients with acute HF (6 randomized controlled trials in 746 patients) reported improvements compared with control (placebo or conventional therapy) in body weight, serum sodium concentration and congestive symptoms, but without effect on short-term (≤30 days) or long-term (>30 days) all-cause death. 26 Our subgroup analyses showed that certain disease/patient factors affect the risk of death. Specifically, hyponatremia severity at baseline, the extent of tolvaptan-induced improvement in hyponatremia, and patients' ability to respond to tolvaptan with increased urine output are associated with lower 6-month all-cause death.…”
Section: Baseline Characteristics According To Outcomementioning
confidence: 81%
“…It exerts its action by inhibiting water reabsorption, leading to aquaresis without affecting electrolyte excretion [7]. The main clinical indication of tolvaptan is the correction of euvolemic and hypervolemic hyponatremia [8], although growing evidence also suggests its efficacy in the management of fluid retention in the setting of acute heart failure [9] and cardiac surgery [10], since it is able to improve congestive symptoms without compromising renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, meta-analyses of tolvaptan have been reported. [10][11][12][13][14] In recent years, several randomized controlled trials (RCTs) performed in actual clinical settings in Japan have also been reported, calling attention to the need for integrated analysis of differences between the doses of tolvaptan used in previous clinical studies in Europe and North America and the doses currently used in Japan. We performed a meta-analysis of RCTs in Europe, North America, and Japan.…”
mentioning
confidence: 99%